Effects of Socially Responsible Behaviors in a Supply Chain under Carbon Cap-and-Trade Regulation - Guobao Zhang (Hindawi Limited, 2021)
Recently, many firms in various industries implement corporate social responsibility (CSR) in different ways. Based on considering a CSR-concerned retailer and an altruistic fairness concern manufacturer, this paper investigates pricing decisions as well as carbon emission policies in a socially responsible supply chain. In this paper, two different modes (the centralized model and decentralized model) are, respectively, conducted and investigated for equilibria. Analytical results reveal that socially responsible retailer (manufacturer) cares more about CSR (altruistic fairness) concern and will increase his counterpart’s pure profit as well as the pure channel profit, ending up with decreasing his own pure profit. The cooperative agents in decentralized scenario can coordinate the channel and achieve the maximum pure channel profit as much as that in a pure profit-maximizing centralized model. Moreover, this paper proposes a novel two-stage carbon cap-and-trade policy for the government and examines how it is affected by the CSR concern level and the altruistic fairness in such a socially responsible supply chain.